The Gansu Muslims of China ([S.l.] : Huang Tu Di Film)
6th episode documentary on Gansu muslim in China. Showa their customs, arts, their life, and their futures
episode 1 A crescent moon - episode 2 The colourful customs - episode 3 The titbits of arts - episode 4 The inevitable change episode 5 A new beginning - episode 6 Way to the future